Hubungan Perilaku Anak Sekolah Dasar dengan Upaya Pencegahan Kejadian Penyakit Diare di Sekolah Dasar Negeri 2 Amolengo Kecamatan Kolono Kabupaten Konawe Selatan - Zuhria, Wa Ode; Mien, Mien (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Based on the results of the initial survey of researchers at SDN 2 Amolengo, Kolono District, Konawe Selatan Regency, data on the number of students totaled 78 students in grades IV - V. Through interviews with 10 students, as many as 7 people (70% of whom received information) did not know correctly how to handle diarrhea. and proper hand washing techniques, while 3 people (30%) knew about handling diarrhea and how to wash hands properly and correctly. Meanwhile, based on student data during 2015 there were 64 cases of sick leave students due to diarrhea, an increase from 2014 which there were 48 cases. The purpose of this study was to determine the relationship between the behavior of elementary school children and efforts to prevent diarrheal diseases at SDN 2 Amolengo, Kolono District, South Konawe Regency. The number of samples is 44 respondents using simple random sampling technique. This research was conducted in May 2016. Based on the results of statistical tests with knowledge variables with a value of X2 count 10,095, attitudes with a value of x2 count of 10,749 and actions with a value of X2 count of 11.145 which can be concluded Ho is rejected and Ha is accepted, thus there is a relationship between the behavior of elementary school children with efforts to prevent the incidence of diarrheal diseases at SDN 2 Amolengo, Kolono District, South Konawe Regency. Thus, it is recommended that schools continue to provide understanding to students so that they continue to pay attention to clean lifestyle behaviors so as to avoid infectious diseases such as diarrhea. For families, it is even more important to pay more attention to children, especially in terms of maintaining health so as to avoid epidemics and the dangers of disease